The Effect of Productivity and Attendance Levels on the Salaries Received by Contract Workers (TKK) (Study in Dinas Pendidikan Kota Bekasi) - Saing, Bungaran; Siahaan, Matdio; Saripudin, Saripudin; Istiantoro, Nugraha; Tukiran, Martinus (Journal of Industrial Engineering & Management Research, 2021)
-This study aims to determine the effect of productivity level and attendance to salary. The object of research is the contract labor (TKK) employees at the Bekasi City Education Office. The quantitative research used questionnaire that distributed to contract labor employees at the Bekasi City Education Agency. The data analysis technique used is multiple regression analysis techniques.The results of the study indicate that the variable Productivity Level has a negative effect on Salary. Furthermore, the Absence Variable has a positive effect on Salary. The results of multiple regression analysis with the function Y = Â¬ 10,087 - 0.052x1 + 0.434x2 + e. and, R Square results of 5.9%, which means 94.1% is the contribution of the variables not examined in this study.